Clinico-Demographic Characteristics and Surgical Outcomes of Thyroid Swelling Patient Attended at a Tertiary Care Hospital in Dhaka City - Sharif, Ahmed; Islam, Md Rabiul; Faruque, Md Golam; Khanam, Rashida Akter; Uddin, Mohammmad Main; Yusuf, Md Abdullah (Journal of Current and Advance Medical Research, 2019)
Background: Thyroid swelling was found in different clinical presentation and demographic characteristics. Objective: The purpose of the present study was to see the clinical and demographic characteristics as well as the surgical outcomes of thyroid swelling patient. Methodology: The study was conducted at Mugda Medical College Hospital, Dhaka during the period of April 2017 to March 2018. The diagnosis of thyroid swelling was based on detailed history, thorough clinical examination and relevant investigations, Ultrasonogram and fine needle aspiration cytology (FNAC). All the patients were undergone surgical management and the outcomes were recorded. All the data were compiled and tabulated in order o obtained a statistical and comprehensive results of the study. Results: A total number of 45 patients were recruited for this study after fulfilling the inclusion and exclusion criteria. This study shows age of the patients ranged from 17 years to 65 years. The highest number of cases (35.6%) belongs to the age group of 31 to 40 years followed by 20% in the age group of 21 to 30 years. Female were higher in frequency (95.6) than male (4.4%). Most of the patients (54%) were from poor socio-economic status. The most common indication were nodular goiter (80%), papillary 13.3%, follicular adenoma 4.4%, and medullary (2.2%). In this study most of the findings showed solid mass in the thyroid gland (55.6%). In this series hemithyroidectomy carried out in 68.9% patients and occupied the top of the list followed by subtotal 22.2%. In this study highest number of complications were recurrent laryngeal nerve paralysis (8.9%). Conclusion: Young adult female patient is most commonly affected by thyroid swelling and mostly are benign nodular type goiter Journal of Current and Advance Medical Research 2019;6(2):97-100